Antitrust Immunity and International Airline Alliances - William Gillespie; Oliver M. Richard (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2011)
Most of the major carriers worldwide have joined one of three international airline alliances. The U.S. Department of Transportation has granted immunity from the U.S. antitrust laws to many carriers within these alliances. This article assesses the competitive effects and efficiencies associated with such grants. A grant of antitrust immunity to carriers in an alliance reduces competition in routes where these carriers offer competing flights, and the data show that fares paid by passengers for travel in non-stop trans-Atlantic flights are higher in routes with fewer independent competitors. The data also show that the alliances can produce pricing efficiencies for trans-Atlantic passengers who travel with connecting itineraries, but antitrust immunity within an alliance is not necessary to achieve such efficiencies.
Keywords: 330